Relationship between WhatsApp usage and employee engagement in Department of National Unity and Integration (JPNIN) - Adzharuddin, Nor Azura; Nagamma, Ys (Penerbit Universiti Kebangsaan Malaysia, 2024)
The usage of technology applications in the workplace has been an escalating phenomenon in which employees use several of these applications for different purposes in relation to work. One of the applications is using WhatsApp as a means of communication among the employees in various departments to ensure effective and fast response from all parties in relation to assigned tasks among the employees. This paper aims to determine the relationship between WhatsApp usage and employee engagement in the Department of National Unity and Integration (JPNIN) in Putrajaya. This research seeks to answer the following research questions: a) what is the level of WhatsApp usage in JPNIN among the staff, b) what is the acceptance level of WhatsApp usage in JPNIN, and c) what is the relationship between WhatsApp usage and employee engagement in JPNIN. This quantitative research is conducted among 274 respondents from JPNIN. The respondents are active users of the WhatsApp application for the communication purposes usage at work. The data was analysed using the Pearson Correlation. This study concludes that all the independent variables which are usage pattern, perceived usefulness, and perceived ease of use, have significant positive relations towards the employee engagement in JPNIN. This study will provide useful insights to JPNIN and other relevant stakeholders that includes the relevant policymakers.